Silicon as a component of ferric oxide scale covering ductile iron pipes after annealing. (July 2021) - Wassilkowska, Anna; Dąbrowski, Wojciech
Highlights: The U.S.A. and European controversy regarding covering or not covering ductile iron external pipe surface with zinc layer. Bond between ductile iron matrix and ferric oxide layers formed during the annealing process of pipes. The role of silicon as an ingredient of ferric oxides in forming protective layer against corrosion. Distribution of silicon in ferric oxide layers covering external ductile iron pipes surface. Abstract: All ductile iron pipe producers use the annealing process to improve the metal structure. It lasts several hours in a hot air atmosphere, when the surface of pipes is covered by ferric oxide scale, consisting usually of two significantly different layers, being the subject of the research reported here. In the U.S.A., commercially produced pipes are not protected by zinc coatings, because it is believed that ferric oxides are not a solid undercoat for such coatings, while the EN 545:2010 standard used in Europe requires the use of zinc or zinc-aluminum coatings, depending on soil corrosivity. To evaluate which approach has more potential, it is necessary first of all to recognize the structure of ferric oxides after the annealing process and then to understand their role as a base for zinc coatings. The microstructure of oxide scales grown on the external surface of industrial ductile iron pipes was investigated using scanning electron microscopy. In the ductile iron matrix, the concentration of silicon is reported to be much lower than in the layer of oxide scale growing directly on the pipe surface. In several samples, some cracks between the oxide layers were not successfully avoided in spite of using a professional saw with a continuous cooling process. Each time the cracks were horizontal and occurred along two boundaries: between the ductile iron matrix and the first oxide layer or between the two oxide layers rich in silicon and essentially silicon free.